The Obligations for Consularization and Legalization of Credit Guarantee Documents Signed in Singapore based on the Regulation of the Minister of Foreign Affairs of the Republic of Indonesia Number 13 of 2019 concerning Procedures for Legalization of Documents at the Ministry of Foreign Affairs (Case Study of PT X Guarantee Document at Bank Y) - Gravita Sari Rahajaan; Arman nefi (IHSA Institute, 2022)
In its implementation, the provision of bank credit cannot be separated from the guarantee provided by the debtor. One type of guarantee that is generally given in the implementation of lending is in the form of a cash guarantee in the guarantor's account which is tied to a pawn account and the signing of an account pawn agreement between the guarantor and the Bank, however, it is not uncommon to find situations where the guarantor will sign the agreement. This pawn is not in Indonesia. Upon the signing of this document abroad, Minister of Foreign Affairs Regulation No. 13/2019 requires the legalization and consularization of these documents, however, with the ratification of the Apostille provisions, there is a view that foreign documents do not need to go through the legalization and consularization process. Therefore, a study was conducted to determine how the validity of foreign documents in the process of granting credit did not go through the consularization and legalization process, and how the consularization and legalization obligations were with the ratification of the apostille convention. This research is a normative juridical research with analytical descriptive typology. The legal materials used are primary and secondary legal materials to be analyzed by qualitative methods. Based on this research, it can be said that the implementation of consularization and legalization of documents in Indonesia does not have a direct sanction and has no effect on the document. And with the ratification of the apostile convention, legalization and consularization of foreign documents is no longer required, however, for documents directly related to commercial activities, consularization and legalization are still mandatory.